Imageable Idioms in Croatian - Broz, Vlatko (Array, 2008)
Imageable idioms are figurative expressions that have associated conventional images or that could call up a conventional scene in the minds of speakers (Lakoff 1987: 447). Based on a similar study of figurative expressions in English (Gibbs 1990), this study investigates mental images associated with idiomatic expressions in the Croatian language. The paper will present a cognitive– linguistic research of selected imageable idioms on a sample of 200 native speakers of Croatian, taking into consideration the variables of age, education, sex and place of origin in Croatia. The research starts from the hypothesis that speakers share tacit knowledge about metaphorical basis for idiomatic expressions that can be recovered by examining speakers’ mental images of those expressions. The questionnaire consisted of 40 questions asking the subjects to explain the meaning of common Croatian figurative expressions and to indicate whether they had come across the given expressions before. Then they were asked to ’ make sense’ of these expressions and find conceptual mappings that link the individual words in those expressions with their figurative meanings. The participants were then asked to form and describe their mental images for the tested idiomatic expressions. For example, there is high consistency in the participants’ image of the idiom ’ pobrkati lon~i}; ; e’ (roughly equivalent to ’ to get the wrong end of the stick’ ) as to the colour and even the pattern on the small pots (the phrase literally means ’ to mix up small pots’ ). Another Croatian idiom in the questionnaire was ’ biti zadnja rupa na svirali’ (whose meaning is close to ’ the fifth/third wheel’ , used for someone who is ignored or not needed by others). The phrase literally means ’ to be the last hole on a musical instrument’ . When the participants were asked what is the total number of the holes on that instrument, their responses were strikingly consistent. The results of the research show to what extent mental images of different idioms overlap and how they account for the motivation of meaning. As expected, a remarkably high degree of consistency in people’ s images and responses points to conceptual metaphors motivating the figurative meanings of the selected idioms. More importantly, this research manages to explicitly articulate what is considered to be a shared tacit knowledge of culture which is in turn reflected in language. References: Gibbs, R. W., & O’ Brien, J. 1990. “ Idioms and mental imagery: The metaphorical motivation for idiomatic meaning” in Cognition, 36, 35– 68 Gibbs, R. W. 1990. “ Psycholinguistic Studies on the Conceptual Basis of Idiomaticity” in Cognitive Linguistics, 1– 4, 417– 51 Gibbs, R. W. 1992. “ What Do Idioms Really Mean?” in Journal of Memory and Language, 31, 485– 506 Lakoff, George. 1987. Women, Fire and Dangerous Things, What Categories Reveal about the Mind. Chicago: Chicago University Press